Presence of gluten and soy derived excipients in medicinal products and their implications on allergen safety and labeling - Alexandra Figueiredo; Maria Deolinda Auxtero; Adriana Brás; Andreia Casimiro; Isabel Margarida Costa (Scientific Reports)
Abstract Gluten and soy allergies are significant health concerns, particularly in individuals with celiac disease or soy sensitivity. While dietary sources of these allergens are well-studied, their presence in medicinal products remains under-explored. This study assessed the prevalence of gluten and soy-derived excipients in 308 medicinal products authorized for marketing in Portugal. A systematic search of the Summary of Product Characteristics (SmPC) database was conducted for 108 analgesics and antipyretics containing paracetamol, 85 NSAIDs containing ibuprofen, and 115 antiasthmatic and bronchodilator medicinal products. The study found significant associations between pharmacotherapeutic groups and the presence of these allergens (p < 0.001). Gluten was more prevalent in the group of analgesics and antipyretics (44.4%) than in NSAIDs (8.2%), whereas soy-derived excipients were more frequent in NSAIDs (14%) than in analgesics and antipyretics (6.5%). No excipients containing gluten or soy were identified in antiasthmatic and bronchodilator medicinal products. In analgesics and antipyretics, 51.2% of solid oral dosage forms and 40% of liquid oral formulations contained gluten. Within the NSAIDs group, gluten was mainly present in liquid oral dosage forms (26.7%). Soy-derived excipients were found in 30% of liquid oral formulations and in 33.3% of rectal dosage forms of analgesics and antipyretics. In the NSAIDs group, soy was more prevalent in liquid oral formulations (26.7%). These findings highlight the need for clearer labeling of allergens in medicinal products and underscore the importance of vigilance for patients with gluten or soy allergies. Further research is required to address gaps in allergen disclosure by pharmaceutical manufacturers and to promote safer medicinal product use for sensitive populations. Enhanced awareness among healthcare providers and patients is essential to mitigate the risk of allergic reactions associated with hidden excipients in medicinal products.